Answer:
-2
Step-by-step explanation:
<u>Step 1: Use PEMDAS</u>
z / 6 + x + x - 5
(6)/6 + (1) + (1) - 5
1 + 1 + 1 - 5
3 - 5
-2
Answer: -2
Answer:
1692
Step-by-step explanation:
2 (4*189 + 90)
=2 (756+90)
= 2 ×846
=1692
Answer:
The answer is 0
Step-by-step explanation:
3n(3m-2n) + 6m^2= (6m-3n)(2n+m)
By expansion
9mn - 6n^2 + 6m^2 = 12mn + 6m^2 -6n^2 - 3mn
By collecting like terms
9mn - 12mn + 3mn - 6n^2 + 6n^2 + 6m^2 - 6 m^2 = 0
-3mn + 3mn=0
Therefore the simplification of the expansion gives us 0
Answer: 16
Step-by-step explanation: 28÷7=4
4×4 = 16